⁶Li-based suspended foil microstrip neutron detectors - Edwards, Nathaniel Scott (Kansas State University, 2018)
The low natural abundance and supply shortage of ³He has resulted in an increase in the cost of ³He. The increase in cost of ³He proportional counters has motived the development of low cost, high efficiency, low gamma-ray sensitivity alternative technologies. A recently developed alternative technology is the ⁶Li-based suspended foil microstrip neutron detector (SFMND) that combines the neutron-conversion and gamma-ray discrimination capabilities of ⁶Li foils with the mechanical robustness and electrical capabilities of microstrip electrodes. SFMNDs differ from Li-foil multi-wire proportional counters because the anode wires are replaced by a single microstrip electrode that improves the mechanical robustness, reduces the microphonic sensitivity, and allows for more ⁶Li foils to be incorporated within a smaller form factor. The first-ever SFMNDs containing one and five 96%-enriched, 75-µm thick ⁶Li foils were fabricated using a silicon microstrip electrode. Neutron-sensitivity testing was performed yielding measured intrinsic thermal-neutron detection efficiencies, εth, of 4.02 ± 0.04% and 14.58 ± 0.11%, respectively. High electrode capacitance and gain instability were exhibited by the silicon microstrip electrode during neutron-sensitivity testing that led to the search for an electrically-stable microstrip-electrode substrate. Schott Borofloat® 33 glass was identified as an electrically-stable substrate and microstrip electrodes were fabricated and characterized. The Schott Borofloat® 33 microstrip electrodes were electrically-stable for a minimum duration of time of approximately 23 hours and had capacitances over an order of magnitude less than the identically sized silicon microstrip electrodes. One- and five-foil SFMNDs were fabricated with a Schott Borofloat® 33 microstrip electrode. Using 96%-enriched, 75-µm thick ⁶Li foils, the one- and five-foil devices had maximum measured εth of 12.58 ± 0.15% and 29.75 ± 0.26%, respectively, with measured gamma-ray rejection ratios of 6.46 x 10⁻⁵ ± 4.32 x 10⁻⁷ and 7.96 x 10-5 ± 4.65 x 10-7 for a ¹³⁷Cs exposure rate of 50 mR hr⁻¹. Devices containing one, five, ten, and twenty 96%-enriched, 75-µm thick ⁶Li foils were simulated using MCNP6 and are theoretically capable of having εth of 18.36%, 54.08%, 65.43%, and 68.36%, respectively. The deviation between measured and simulated εth is suspected to occur due to the electric field strength distribution, electron attachment, microstrip-electrode capacitance, or any combination thereof and solutions for each of these suspected concerns are described.
Keywords: Neutron detection; Radiation detection; Microstrip electrodes; Lithium foil; Device characterization; Gas-filled neutron detector